Epidemiology of football-related injuries in young male football players. An additional analysis of data from a cluster-randomised controlled trial - Obërtinca, R.; Meyer, T.; Aus der Fünten, K. (Science and Medicine in Football, 2025)
Football carries a high risk of injury for youth players. The aim of this study was to investigate the epidemiology of football-related injuries in young male players. The data stems from a previously conducted cluster-randomised controlled trial that investigated the efficacy of `FUNBALL`, a new injury prevention programme. This study contains the data of the 503 players of the control arm. The players belonged to 22 football teams of the Under-(U)15, U17 and U19 age groups. The time-loss injuries were recorded during the season 2021-2022 according to the Football Consensus Statement. An analysis on the injury incidence (IR, calculated per 1000 hours of exposure), location, severity, category, and type was performed. Incidence rate ratios (IRRs) were used to compare the variables between the specific age groups. 187 injuries (96 in training and 91 in matches) occurred during 52 938 hours of exposure. The overall IR was 3.53 injuries/1000 h (95% confidence intervals (CI) 3.06 to 4.07). The training IR was 2.16 injuries/1000 h (95% CI 1.17 to 2.64). The match IR was 10.50 injuries/1000 h (95% CI 8.55 to 12.89). In the U19s, the overall IRR was higher compared to the U17s (IRR 1.57, CI 1.12 to 2.19; p = 0.008) and compared to the U15s (IRR 1.82, 95% CI 1.25 to 2.62; p = 0.001). The thigh was the most commonly affected body region (IR 0.92/1000 h, 95% CI 0.69 to 1.22). Muscle injuries were the most common injury type (IR 1.05/1000 h, 95% CI 0.81 to 1.37). Injury burden was 74 lost days/1000 h. The findings of this study indicate a lower injury incidence in youth players than in adult ones. We observed a higher injury incidence towards the older age groups.